Safety and efficacy of the 5-lipoxygenase-activating protein inhibitor AZD5718 in patients with recent myocardial infarction: The phase 2a FLAVOUR study. (15th October 2022) - Prescott, Eva; Angerås, Oskar; Erlinge, David; Grove, Erik L.; Hedman, Marja; Jensen, Lisette O.; Pernow, John; Saraste, Antti; Åkerblom, Axel; Svedlund, Sara; Rudvik, Anna; Knöchel, Jane; et al.
Abstract: Background: Leukotrienes are pro-inflammatory vasoactive lipid mediators implicated in the pathophysiology of atherosclerotic cardiovascular disease. We studied the effect of the 5-lipoxygenase-activating protein inhibitor AZD5718 on leukotriene biosynthesis and coronary microvascular function in a single-blind, phase 2a study. Methods: Patients 7–28 days after myocardial infarction (±ST elevation), with <50% left anterior descending coronary artery stenosis and Thrombolysis in Myocardial Infarction flow grade ≥ 2 after percutaneous coronary intervention, were randomized 2:1:2 to once-daily AZD5718 200 mg or 50 mg, or placebo, in 4- and 12-week cohorts. Change in urine leukotriene E4 (uLTE4 ) was the primary endpoint, and coronary flow velocity reserve (CFVR; via echocardiography) was the key secondary endpoint. Results: Of 129 randomized patients, 128 received treatment (200 mg, n = 52; 50 mg, n = 25; placebo, n = 51). Statistically significant reductions in uLTE4 levels of >80% were observed in both AZD5718 groups versus the placebo group at 4 and 12 weeks. No significant changes in CFVR were observed for AZD5718 versus placebo. Adverse events (AEs) occurred in 12/18, 3/6 and 6/13 patients receiving 200 mg, 50 mg and placebo, respectively, in the 4-week cohort, and in 27/34, 14/19 and 24/38 patients, respectively, in the 12-week cohort. Serious AEs in seven patients receiving AZD5718 and four receiving placebo were not treatment-related, and there were no deaths. Conclusions: In patients with recent myocardial infarction, AZD5718 was well tolerated, and leukotriene biosynthesis was dose-dependently inhibited. No significant changes in CFVR were detected. ClinicalTrials.gov identifier: NCT03317002. Graphical abstract: Unlabelled Image Highlights: Leukotrienes are implicated in the pathophysiology of atherosclerotic CV disease. AZD5718 is a 5-lipoxygenase-activating protein inhibitor. In patients with recent myocardial infarction, AZD5718 was well tolerated. AZD5718 significantly reduced leukotriene E4 levels compared with placebo.